Synthesis of pyrazole and 1,3,4-oxadiazole derivatives of pharmaceutical potential - Kadam, Mayur; Jadhao, Nitin L.; Gajbhiye, Jayant M. (Prospects in Pharmaceutical Sciences, 2024)
Heterocyclic compounds are important molecules that serve as scaffolds or linkers for the core structure of numerous drug substances. In particular, pyrazole and 1,3,4-oxadiazole are compounds of great interest due to their comprehensive biological activities and interesting structural features. Here, we described an efficient and economical synthetic route leading to N-phenyl substituted pyrazole and 1,3,4-oxadiazole derivatives. Retrosynthetic disconnective analysis showed that the N-phenyl substituted pyrazole can be obtained from chalcone, accessible from the respective aldehyde, and acetophenone. The disubstituted 1,3,4-oxadiazole can be constructed from the respective aldehyde, which originates from pyrrole-containing compound, and formyl chloride. Based on our retrosynthetic analysis, N-phenyl substituted pyrazole was obtained by cyclization of the respective chalcone with phenylhydrazine to give pyrazoline which was in turn converted into pyrazole by oxidative aromatization. Potassium carbonate and a catalytic amount of molecular iodine were used to oxidatively cyclize semicarbazones into 1,3,4-oxadiazoles in a transition metal-free process. Novel pyrazole and 1,3,4-oxadiazoles with potential biological activity are investigated as antituberculosis, anticonvulsant, antidiabetic, anticancer, and tyrosinase inhibitory agents.